Interpretative Phenomenological Analysis on Difficulties Encountered and Self-Efficacy in Science Lessons with Mathematical Computation among Grade 7 Learners - Solis, Alexis; Uy, Edison (JPAIR Multidisciplinary Research, 2026)
This qualitative study investigated the difficulties encountered and the level of self-efficacy of Grade 7 learners in Science lessons containing mathematical computation at Pangdan National High School, Catbalogan IX District, Schools Division of Catbalogan City, during the school year 2023–2024. Anchored on Bandura’s Social Cognitive Theory and Achievement Goal Theory, the study aimed to provide an in-depth understanding of learners’ experiences in handling computation-based science tasks. Using an interpretative phenomenological design, fifteen purposively selected slow and struggling learners participated in content analysis activities, problem-solving tasks based on Polya’s method, and focus group discussions. Findings revealed that mathematical computation appeared only in selected Grade 7 Science topics, particularly motion, motion graphs, and light characteristics, while topics such as sound characteristics, heat transfer, and charging processes lacked computational components. Learners exhibited varied proficiency levels: some demonstrated strength across all stages of Polya’s framework, whereas others struggled in understanding problems, planning solutions, performing computations, and verifying results. Thematic analysis showed that self-efficacy was influenced by curiosity in science, difficulties with computation-heavy topics, effective teaching strategies, and strong support from teachers, peers, and family. The study concludes that integrating computation in underrepresented topics, reinforcing verification practices, and applying targeted instructional strategies are essential to enhance problem-solving skills and self-efficacy in science.